Avaliação das técnicas de isolamento da massa celular interna de blastocistos para obtenção de células-tronco pluripotentes - Renata de Lima Bossi (2011)
Embryonic stem cells are classified as pluripotent and are able to differentiate into many of cell types and tissues from three germ layers.They represent an alternative for treatment and even cure of many diseases. Until now many different forms to isolate the inner cell mass have been tested, but none have shown to be a better option. Therefore theaim of this study was to evaluate different methods of stem cells isolation from a blastocyst's inner cell mass, using mechanical, laser, immunosurgery and whole blastocyst culture.Twenty seven embryos were donated for this research. One embryo (3,7%) was mechanically isolated; 3 (11.1%) were isolated by immunosurgery, 2 (7.4%) were isolated by laser and 21 (77.8%) bywhole blastocyst culture.Cell adhesion was confirmed 48 hours after cells plating. Nineteen (70%) isolated inner cell mass were attached in plates with Matrigel solution.We observed that after whole blastocyst culture, 81% of the cells were attached in plates; after immunosurgery, cell adhesion was 33% and after mechanical isolation the cell adhesion was increased 100%.Cellular adhesion was not observed when the cells were isolated by laser technique.A total of sixteen blastocysts presented good quality, expanded blastocoele and inner cell mass compact,large and distinguishable.Eleven blastocysts presented low quality, with small blastocoele and tiny or indistinguishable inner cell mass.No significant differences were observed in cellular adhesion when comparing the day of inner cell masss isolation on day 5 or 7 blastocysts (66,7% x 77,8% , P=0,67).Rates of cell adhesion were not significantly different when we compared the methods of zona pellucida removal by laser or Pronase (33,3% x 75%, P= 0,20).Cellular adhesion was significantly higher when good quality blastocysts were used (87,5% x 63,6%, P= 0,011). We can conclude that whole blastocyst culture is easily applicable and highly efficient for isolation of embryonic stem cells.